Efektivitas Edukasi Fiqih Lingkungan Muhammadiyah terhadap Peningkatan Pengetahuan PHBS Santriwati: Studi Pra–Pascaintervensi di PP Taruna Al-Qur’an - 'Aabidah Ummu 'Aziizah; Imam Suyuti; Safika Maranti; Bekti Wulan Sari (Universitas Ahmad Dahlan, 2026)
Islamic boarding schools (pesantren) frequently exhibit a persistent gap between environmental health compliance and internalized theological conviction. This gap explains why healthy and clean behaviors (PHBS) developed within the pesantren rarely persist once students return home. This study evaluated the effectiveness of Muhammadiyah Environmental Fiqh-based education in improving PHBS knowledge among female students at PP Taruna Al-Qur’an, Sleman. Employing a pre–post intervention design with Normalized Gain (N-Gain) analysis, 188 female students participated in a structured educational intervention delivered in a single 400-minute session. Pre-test results showed a mean correct-answer rate of 10% (very low category), while post-test results reached 93% (very high category). The N-Gain Score of 0.92 fell within the high effectiveness category according to Hake’s criteria, indicating that 92% of the available learning space was successfully filled. The study also confirmed that Muhammadiyah Environmental Fiqh, rooted in universally applicable Quranic principles, can be effectively adopted by non-AUM pesantren institutions. These findings affirm that theological framing is not merely normatively meaningful but also pedagogically superior in health education interventions within Islamic educational settings.